اضطراب تشتت الانتباه والنشاط الزائد لدى الأطفال - غربي جهاد; ساعد شفيق (University of Eloued جامعة الوادي, 2024)
ركزت هاته الورقة البحثية على أحد أهم الموضوعات النفسية والسلوكية عند الأطفال وهو اضطراب تشتت الانتباه والنشاط الزائد، يظهر في مرحلة الطفولة ويستمر معها حتى البلوغ والرشد بأشكال وأعراض مختلفة وأكثر تعقيدا، ومن هنا جاءت أهمية إجراء هاته الدراسة من خلال تقديم مقاربة نظرية شاملة تضمنت مختلف الجوانب الطبية والنفسية والتربوية لاضطراب تشتت الانتباه والنشاط الزائد، حيث تمت مناقشة المفاهيم والتعريفات والأنواع والنظريات المفسرة وغيرها من النقاط المهمة الخاصة بهذا الاضطراب وصولا إلى التشخيص والعلاج، ومن خلال هذه الدراسة خلص الباحثان إلى أن اضطراب تشتت الانتباه والنشاط الزائد هو اضطراب معقد يصيب الأطفال، تعددت أسبابه وأنواعه وزادت نسب انتشاره مؤخرا، لذلك تعتبر عملية التدخل المبكر والتشخيص الدقيق من أجل تقديم سبل العلاج المتنوعة والتي تعتبر أهمها العلاج الطبي والسلوكي، أهم خطوة يحتاجها الأطفال المصابين بهذا الاضطراب للحد من انتشاره والتخفيف من أعراضه في مراحله الأولى. Abstract: This research paper focused on one of the most important psychological and behavioral topics in children, which is attention deficit disorder and hyperactivity, It appears in childhood and continues into adulthood with different and more complex forms and symptoms. Hence the importance of conducting this study by presenting a comprehensive theoretical approach that includes various medical, psychological and educational aspects of attention deficit hyperactivity disorder, Concepts, definitions, types, explanatory theories, and other important points related to this disorder were discussed, leading to diagnosis and treatment, Through this study, the researchers concluded that attention deficit hyperactivity disorder is a complex disorder that affects children, its causes and types are numerous and its prevalence rates have increased recently. Therefore, the process of early intervention and accurate diagnosis in order to provide various treatment methods, the most important of which is medical and behavioral treatment, is considered the most important step. Children with this disorder need it to limit its spread and alleviate its symptoms in its early stag
مقاربة نظرية
Keywords: اضطراب; تشتت الانتباه; نشاط زائد; تشخيص; أطفال; disorder; attention deficit disorder; hyperactivity; diagnosis; children